WOMEN AND MAKE-UP: THE DILEMMA OF BOURDIEU'S SUBJECTIVISM-OBJECTIVISM ON SOCIAL MEDIA - Suharnanik, Suharnanik (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
This research refers to the trend of women's makeup in the 2020 era, which is dominated by natural makeup. Influencers and makeup artists have a role in popularizing it. The author is interested in examining the makeup behavior in women with Bourdieu's theory. What behaviors make a woman look natural, prioritize skin health, minimal makeup. What culture is behind it. The findings of this study are all women like makeup, habitus leads to natural makeup. Habitus emphasized freedom in analyzing a practice as an agent and social structure. Women have a habitus in using makeup determined by a dual mechanism not just the dominance of social media factors, but also played by self-freedom as women as influencers in the social media itself. The arena is an environment where strength is at stake in the struggle over capital resources. Social media is an arena, a different social space, more enabling women to compete more dynamically in gaining position and legitimacy. Women use practices in makeup as a strategy in winning a competition. The makeup practice is an accumulation of women's capital and habitus, where every woman is different in her practice. The method used in this research includes in-depth interviews with women who use makeup, as well as literacy studies of the concepts of capital, habitus, and the realm. The results showed that women undergoing their practice experienced